Meat Quality, Blood Profile, and Fecal Ammonia Concentration of Broiler Supplemented with Liquid Smoke - F Yosi; S Sandi (Faculty of Animal Science, Bogor Agricultural University, 2014)
Liquid smoke is one of the feed additive that can be given to animals. The aim of the study was to determine the influence of liquid smoke given through drinking water on meat quality and production of fecal ammonia in broiler. Variables observed were meat pH, water holding capacity, cooking loss, the tensile strength of meat, cut off strength of meat, blood urea nitrogen and creatinine concentrations, and fecal ammonia. The experiment was assigned in a completely randomized design with 5 treatments, and 4 equal replicates. The treatments tested were symbolized as R0, R1, R2, R3, and R4, based on the level of liquid smoke added into drinking water (v/v) namely, 0%, 0.25%, 0.50%, 0.75%, and 1.00%, respectively. The data were subjected to analysis of variance, and continued to Duncan’s multiple range test to determine the difference between treatment mean values at 5% probability. The results indicated that addition of liquid smoke up to 1% did not affect the meat pH, water holding capacity, cooking loss, the tensile strength of meat, blood urea nitrogen, and creatinine content, but it decreased the cut off strength of meat and fecal ammonia. It was concluded that an optimal dose of granting liquid smoke through drinking water was 1%.Key words: liquid smoke, broiler, meat quality, fecal ammonia